THE EFFECT OF PHALERIA MACROCARPA ETHNIC FOOD COMPLEMENTARY TO DECREASE BLOOD PRESSURE - Rizal, Muhammad Fathur; Haryanto, Joni; Has, Eka Mishbahatul Mar'ah (Universitas Airlangga, 2020)
Introduction: Hypertension is one of degenerative disease that is often found in the elderly group. Many studies have been developed to reduce blood pressure, including complementary therapies. One of the complementary therapies is by utilizing Phaleria Macrocarpa. This study was aimed to explain the effect of Phaleria macrocarpa ethnic food complementary to decrease blood pressure of elderly with hypertension. Methods : Design used in this study was quasy experiment design. The population was the elderly with hypertension in UPT PSTW Blitar (in Blitar and Tulungagung). Total sampel was 40 respondens, taken according to inclusion criteria. The independent variabel was Phaleria macrocarpa ethnic food complementary. The dependent variabel was blood pressure. Data were collected using measurement blood pressure and made ethnic food complementary with Standart Operational Procedure. Data were analzed using paired t-test and ANOVA with level of significance of â‰¤ 0,05. Results : The Results showed that there were effect of giving intervention by ethnic food complementary with phaleria macrocarpa fruit, leaf, or mixed (fruit and leaf) to decrease blood pressure (systolic, diastolic, and MAP). Conclusion : This intervention can be used as a complementary therapy herbal to decrease high blood pressure.